All in the Family: Primary Megakaryocytes for Studies of Platelet αIIbβ3 Signaling - Shattil, Sanford J.; Leavitt, Andrew (Thrombosis and Haemostasis, 2001)
Integrin αIIbβ3 mediates key platelet adhesive responses during hemostasis and thrombosis. Adhesive ligand binding to αIIbβ3 is regulated by “inside-out” signals, while adhesion-dependent cytoskeletal events are regulated by “outside-in” signals from αIIbβ3. Currently, the molecular basis of bidirectional αIIbβ3 signaling is incompletely understood. The functional assessment of integrin signaling pathways in nucleated cells has been facilitated by techniques such as viral transduction which enable expression of dominant-active and dominant-inhibitory gene products. This approach cannot be used with anucleate platelets. However, recent advances in the ability to expand human and murine megakaryocytes from hematopoietic stem cells provide a tractable and genetically manipulatable system for studies of αIIbβ3 signaling. This overview will discuss some of the advantages and limitations of this approach and provide examples of its utility. Thus, in addition to their intrinsic value for understanding hematopoiesis and platelet formation, primary megakaryocytes represent a model system complementary to platelets for unraveling the remaining mysteries of αIIbβ3 signaling.
Keywords: αIIbβ3; integrin; megakaryocyte; platelet; signaling